Pengaruh Penggunaan Teknologi Pendidikan terhadap Efektivitas Pembelajaran di Perguruan Tinggi: Studi Kualitatif di Universitas Negeri Medan - Hadad Alwi Hadinata; Ashfi Raihan; Rendi Kurniawan; Elia Noventa Tarigan (Lembaga Pengembangan Kinerja Dosen, 2025)
This qualitative study explores in-depth the perceptions of students at Universitas Negeri Medan (UNIMED) regarding the influence of educational technology (EdTech) on their learning effectiveness. Amidst the global digital transformation, the integration of digital tools in higher education has become a strategic need to improve the quality of learning. This study used an interpretive phenomenological approach, with semi-structured interviews with 18 undergraduate students from various faculties as the primary data collection method. Data were analyzed through thematic analysis to identify patterns and meanings. The results show that EdTech, through the SIPDA platform, improves accessibility of learning resources, schedule flexibility, and collaboration, but is still hampered by limitations in infrastructure, digital literacy, and pedagogical integration. This study provides contextual insights from Indonesia, with practical recommendations to improve the implementation of EdTech at UNIMED and similar institutions.